Treatment of micropollutants in water and wastewater - Virkutyte, Jurate; Varma, Rajender S.; Jegatheesan, Veeriah (Integrated environmental technology series., 2010)
This book will give a comprehensive overview of modern analytical methods and will summarize novel single and hybrid methods to remove continuously emerging contaminants - micropollutants from the aqueous phase.